Recent development in Extended Reality technologies - Vivekanandam, B. (Recent Research Reviews Journal, 2023)
This study discusses the recent trends in Extended Reality (XR) technologies. Extended Reality is a group of three technologies i.e., virtual reality, augmented reality, and mixed reality. It has been used in many high-performance applications like military, gaming and medicine. In general, all immersive technologies increase the sense of realism, by fusing the virtual and real worlds. The same underlying technologies that enable AR and VR also power XR to deliver a wide range of innovative user experiences. According to Qualcomm, the future of XR is to develop sleek headsets to revolutionize user experiences on a daily basis and also in many different market segments, including education, retail, and healthcare. This study summarizes the different types of extended reality technologies, XR standardization work, XR and its multi-interactive technologies, and implementation of XR in real life applications.